Host age as predisposing factor for incidence of black leaf spot of cauliflower caused by Alternaria brassicae and Alternaria brassicicola - PRATIBHA SHARMA*, SWATI DEEP and (Indian Phytopathology, 2012)
The age of host leaf and pathogenic nature are very important parameters while evaluating large number of isolates against any crop germplasm. Keeping this in view, three varieties of cauliflower viz., Pusa Deepali, Pusa Meghna and Pusa Sharad were evaluated using detached leaf method, for level of infection by twenty-two isolates of A. brassicae (16) and A. brassicicola (6) collected from different states of India. Four different ages of leaves viz- 15, 30, 45 and 60-day were evaluated for their comparative susceptibility to the pathogens. Percent Disease Index values differed significantly and disease was expressed only in 60-day old leaves with no symptoms in 45-day old leaves, clearly indicating susceptibility of matured leaves. All six A. brassicicola isolates infected both 45 and 60 days old leaves while full infection of Alternaria brassicae was found only on 60 days old leaves.